Caspase-12 Is Present During Craniofacial Development and Participates in Regulation of Osteogenic Markers - Vesela, Barbora; Kratochvilova, Adela; Svandova, Eva; Benes, Petr; Rihova, Kamila; Poliard, Anne; Matalova, Eva (Frontiers in Cell and Developmental Biology, 2020)
Caspases are evolutionary conserved proteases traditionally known as participating in apoptosis and inflammation but recently discovered also in association with other processes such as proliferation or differentiation. This investigation focuses on caspase-12, ranked among inflammatory caspases but displaying other, not yet defined functions. A screening analysis pointed to statistically significant (P<0.001) increase in expression of caspase-12 in a decisive period of mandibular bone formation when the original mesenchymal condensation turns into vascularized bone tissue. Immunofluorescence analysis confirmed the presence of caspase-12 protein in osteoblasts. Therefore, the osteoblastic cell line MC3T3-E1 was challenged to investigate any impact of caspase-12 on the osteogenic pathways. Pharmacological inhibition of caspase-12 in MC3T3-E1 cells caused a statistically significant decrease in expression of some major osteogenic genes, including those for alkaline phosphatase, osteocalcin and Phex. This downregulation was further confirmed by an alkaline phosphatase activity assay and by a siRNA inhibition approach. Altogether, this study demonstrates caspase-12 expression and points to its unknown physiological engagement in bone cells during the course of craniofacial development.